PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP KEMAMPUAN MEMAHAMI TEKS CERPEN SISWA KELAS VII SMP NEGERI 3 PAYAKUMBUH - Yetti, Nofrida; Atmazaki, Atmazaki; Tamsin, Andria Catri (Universitas Negeri Padang, 2016)
Abstract This research aims to (1) describe grade ability to understand short story text of students class VII SMP Negeri 3 Payakumbuh before application cooperative learning NHT type, (2) describe grade ability to understand short story text of students class VII SMP Negeri 3 Payakumbuh after application cooperative learning NHT type, (3) describe the effect of the use of cooperative learning NHT type, toward students’ ability to understand short story text of students class VII SMP Negeri 3 Payakumbuh. The type of this research is quantitative research done using experimental design. There are three results of the research are (1) the students’ ability to understand short story text before application cooperative learning NHT type at class VII SMP Negeri 3 Payakumbuh is more fairly and grades C with average 63,08, (2) the students’ ability in to understand short story text before application cooperative learning NHT type at class VII SMP Negeri 3 Payakumbuh is good and grades B with average 76,00, and (3) based on t-test, alternative hypothesis (H1) is gained at the significant phase 95% and degrees of freedom (df)=(n-1) because tcount> t-table (7,83>1,70). Kata kunci : pengaruh, kooperatif, numbered head together (NHT), dan cerita pendek